Menilik Himbauan Pemerintah Terkait Pinjaman Online Ilegal Perspekif Fikih Muamalah - Khoirotul Adabiyah (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
Seeing the large number of cases and fatalities found due to illegal lending, the government finally issued an appeal to the public not to pay their debts from illegal lending services. The purpose of this research is to find out the muamalah fiqh review of the government's appeal regarding the prohibition on paying illegal loan debts, as well as to find out the benefits that exist for the government, debtors and creditors of illegal loans. This research method uses a qualitative method that examines the muamalah fiqh review of the government's appeal regarding the prohibition on paying illegal loan debts, with a type of library research using descriptive analysis methods. The results of this research show that illegal loan debtors are still obliged to pay